La cultura de los espacios socialistas. Casas del Pueblo y Centros obreros en la Segunda República española - Diego Caro Cancela (Cahiers de Civilisation Espagnole Contemporaine)
This article analyzes the growth of the Socialist Party and its cultural practices in the Second Spanish Republic. It describes the activities of the «House´s People» and the appearance of tens of new newspapers connected to psoe and ugt. Finally, it values the appearance of new cultural actions and the suppression of the conservative biennium